How to apply User-generated content for TV news report - Sroysri, Panadda (Journal of Digital Communications, 2020)
The changing of media landscape has resulted in variation of communication channels and also causes ethical problem in content presentation. In particular the content from online media that used in TV news report. The study aims to study how news reporter use information from online media to report on television and compare the Guidelines and Ethical Standards for using information from online media in news production process to identify supporting factors and limitations from using information for news report on television. The data were collected from documentary research and in-depth interview with news reporters from TV stations and compared to the Guidelines in order to find supporting factors and limitations to develop knowledge for news production. The study found that operating method of news organization is divided into information management, news angle selection, data analysis, retrieving sources and presentation. In comparison to the Guidelines, it found that supporting factors consist of; consistency of workflow pattern, definition of news objectives, selection of trusted sources, checking information from various sources and concerning impact on news sources. Meanwhile the limitations consist of; different skills in the field of expertise, considering the news value, utilization of technology, working under time limitation, and monetizing corporate policies. Recommendation on the event of crisis, reporters should analyze data carefully before reporting to prevent confusion in society, and media organizations should encourage reporters to analyze online content carefully with media literacy.